2016
DOI: 10.5116/ijme.5749.7b8b
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes and acceptability of near-peer teaching among medical students in clinical skills

Abstract: ObjectivesTo determine the outcomes and acceptability of final-year students tutoring in Clinical Skills to Years 1-2 students in a 4-week Medical Education elective. MethodsA paper-based survey with 14 questions requiring responses on a Likert-like scale and 2 questions with free-text responses was used to investigate Year 6 student-tutor (n=45) and Years 1-2 tutee (n=348) perceptions of near-peer teaching in Clinical Skills. The independent t-test compared mean responses from student-tutors and tutees, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 14 publications
4
44
1
1
Order By: Relevance
“…As expected, student tutors were perceived as socially congruent when students felt free to ask questions directly [16,37,38]. Further, student tutors could increase the students' motivation by showing social congruence, which was also reported by Khaw [39]. All three groups reported that student and student tutors shared similar social roles, as they were able to identify with each other, which might have an impact on social congruence [1,25,27].…”
Section: Discussionmentioning
confidence: 54%
“…As expected, student tutors were perceived as socially congruent when students felt free to ask questions directly [16,37,38]. Further, student tutors could increase the students' motivation by showing social congruence, which was also reported by Khaw [39]. All three groups reported that student and student tutors shared similar social roles, as they were able to identify with each other, which might have an impact on social congruence [1,25,27].…”
Section: Discussionmentioning
confidence: 54%
“…Anatomy has been suggested to be one of the more flexible courses that is more open to new teaching methods, such as PAL (Evans and Cuffe, 2009; Erie et al, 2013). Although peer teaching has been used in various physiology and pathophysiology courses, as well as clinical courses, the literature still remains sparse (Kibble, 2009; Khaw and Raw, 2016; Gottlieb et al, 2017). While peer teaching has been relatively widely used in anatomy, few studies have evaluated peer teaching programs across entire terms or academic years, as the present study does.…”
Section: Discussionmentioning
confidence: 99%
“…The GMC [5] indicates that students "gain coping strategies by talking to their peers and from clinicians who are brought in to talk about real-life experiences [and] who have made mistakes". Studies on such 'near-peer' session facilitation support the GMC stance [14,15]. Moreover, it has been shown that students "want to hear from 'real' professionals, not archetypes" and in doing so can better develop coping strategies [16].…”
Section: The Role Of Clinical Educatorsmentioning
confidence: 99%